ANALISIS USAHATANI PADI LADANG BERPINDAH DI DESA PEJALIN KECAMATAN TANJUNG PALAS KABUPATEN BULUNGAN PROVINSI KALIMANTAN UTARA (Analysis of Paddy Farming in Shifting Cultivation in Pejalin Village Tanjung Palas Subdistrict Bulungan District North Kalimantan Province) - NILA RUSYANTI; DIDI ADRIANSYAH; SITI ROSMINA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2018)
Most community of Pejalin Village has profession as paddy farmers in shifting cultivation. Farmers  in Pejalin Village cultivate paddy with some varieties such as E’ho, Libang, and Usunuan. Some farmers in Pejalin Village sometimes use a lot of inputs, they hope to get high yield. However, the use of a lot of inputs will increase production cost then decrease profit of farming. This research aimed to analysis paddy farming in shifting cultivation by using the varieties of E’ho, Libang, and Usunan. Method that used in this research was method of descriptive qualitative. Determination of sampling uses cencus sampling with 35 respondents. The result of this research showed high cost in farming of Libang variety with cost as much as IDR3,060,725.00 then E’ho variety with cost as much as IDR2,900,687.00 and Usunuan variety with cost as much as IDR2,335,816.00.  The highest income in farming of E’ho variety as much as IDR6,348,785.00 then Libang variety as much as IDR5,203,175.00 and Usunuan variety as much as IDR4,514,530.00 in a planting season. R/C ratio was 3 showed paddy farming that done by farmers is feasible and profitable.